Total Body Potassium in Non-Dialysed and Dialysed Patients with Chronic Renal Failure. Issue 5803 (25th March 1972) - Boddy, Keith; King, Priscilla C.; Lindsay, Robert M.; Briggs, James D.; Winchester, James F.; Kennedy, Arthur C.
Abstract : Total body potassium was studied in 33 patients with chronic renal failure, 18 of whom had been receiving regular dialysis therapy for 1 to 48 months. In nondialysed patients body potassium was not significantly different from normal in the group as a whole, but was significantly greater than normal in three patients, and significantly less than normal in two patients. In 14 of the dialysed patients, both as individuals and as a group, body potassium was not significantly different from normal but in the remaining four it was less than normal. Potassium transfer during dialysis was studied in two patients. Uptake by these two patients of 43 K added to the dialysate (1 mEq K/litre) was measured by whole-body monitoring. Transfer of administered 43 K from the patients to the dialysate was measured by whole-body monitoring and by radioactive and chemical assay of the dialysate. A negative balance due to twice-weekly dialysis of 178 and 244 mEq K/week was found, which with weekly faecal and urine losses of 20-30 mEq K approximately equals the dietary intake of 210-315 mEq K.